2020
DOI: 10.1089/can.2019.0103
|View full text |Cite
|
Sign up to set email alerts
|

Nausea-Induced Conditioned Gaping Reactions in Rats Produced by High-Dose Synthetic Cannabinoid, JWH-018

Abstract: Introduction: Cannabinoid hyperemesis syndrome is becoming a more prominently reported side effect of cannabis containing high-dose D 9-tetrahydrocannabinol (THC) and designer cannabinoid drugs such as ''Spice.'' One active ingredient that has been found in ''Spice'' is 1-pentyl-3-(1-naphthoyl)indole (JWH-018), a synthetic full agonist of the cannabinoid 1 (CB 1) receptor. In this study, we evaluated the potential of different doses of JWH-018 to produce conditioned gaping in rats, an index of nausea. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Plasma corticosterone levels were determined using an ELISA as previously described, according to the manufacturer's protocol (Cayman Chemical Company, Ann Arbor, Michigan, USA, #500655, RRID: AB_2868564 —for restraint and swim stress cohorts ( Vecchiarelli et al, 2015 ); Arbor Assays, Ann Arbor, Michigan, USA, C#K014–H, RRID: AB_2877626 —for the foot shock stress cohort ( DeVuono et al, 2020 )).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma corticosterone levels were determined using an ELISA as previously described, according to the manufacturer's protocol (Cayman Chemical Company, Ann Arbor, Michigan, USA, #500655, RRID: AB_2868564 —for restraint and swim stress cohorts ( Vecchiarelli et al, 2015 ); Arbor Assays, Ann Arbor, Michigan, USA, C#K014–H, RRID: AB_2877626 —for the foot shock stress cohort ( DeVuono et al, 2020 )).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, in the current population of recreational cannabis users, a novel cannabis-induced hyperemesis syndrome has been attributed to ingestion of very high doses of THC. The mechanism is poorly understood, but it has been suggested that prolonged exposure to high doses of THC might down-regulate CB 1 R or otherwise perturb the endogenous regulation of vomiting centers in the brain stem and/or elicit stress mechanisms at the hypothalamic-pituitary axis (Galli et al, 2011;DeVuono et al, 2020). Thus, there may be a "bell-shaped" dose-response curve suggesting multiple mechanisms for the anti-versus pro-nausea/vomiting endpoints.…”
Section: Table 4 Placeholdermentioning
confidence: 99%
“…The effects of stroboscopic light synchronized or unsynchronized to the acceleration–deceleration phase of rotation were examined, and the influence of color temperature and lighting intensity was also observed. MS-related gastrointestinal responses were assessed by measuring conditioned gaping and defecation responses due to the absence of vomiting reaction in rodents (Wang et al, 2012 , 2017 ; Zhou et al, 2017 ; Qi et al, 2019 ; Devuono et al, 2020 ). Motor and balance performance were evaluated using spontaneous locomotion test and balance beam test (Manno et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%